Interleukin 10 and Heart Fatty Acid-Binding Protein as Early Outcome Predictors in Patients With Traumatic Brain Injury - Lagerstedt, Linnéa; Azurmendi, Leire; Tenovuo, Olli; Katila, Ari J.; Takala, Riikka S. K.; Blennow, Kaj; Newcombe, Virginia F. J.; Maanpää, Henna-Riikka; Tallus, Jussi; Hossain, Iftakher; Gils, Mark van; Menon, David K.; et al. (Frontiers in Neurology, 2020)
Background: Patients with traumatic brain injury (TBI) have variable and unpredictable outcome. The proteins interleukin 10 (IL-10) and heart fatty acid-binding protein (H-FABP) have shown predictive value for the presence of intracranial lesions. Aim: To evaluate the individual and combined outcome prediction ability of IL-10 and H-FABP, and to compare them to the more studied proteins S100B, glial fibrillary acidic protein (GFAP) and neurofilament light (NF-L), both with and without clinical predictors. Methods: Blood samples from patients with acute TBI (all severities) were collected <24h post trauma. Outcome was measured >6 months post injury using the Glasgow Outcome Scale Extended (GOSE) score dichotomizing patients into: (i) those with favorable (GOSE≥5)/unfavorable outcome (GOSE≤4) and complete (GOSE=8)/incomplete (GOSE≤7) recovery, and (ii) patients with mild TBI (mTBI) and patients with TBIs of all severities. Results: When sensitivity was set at 95-100%, S100B had the best specificity (44%) in identifying patients with unfavorable outcome among patients with mTBI, while IL-10 had the best specificity (50%) in patients with all severities. In predicting patients with incomplete recovery, H-FABP showed specificity of 4% in patients with mTBI and 28% in TBIs of all severities. In predicting unfavorable outcome, a model consisting of S100B, age and injury severity score (ISS) yielded a specificity of 89% in cases with mTBI, and a model including IL-10, age and clinical TBI severity reached a specificity of 80% in patients with all severities. In predicting incomplete recovery, a model including H-FABP, NF-L and ISS yielded a specificity of 56% (in mTBI), and a model including H-FABP, age and ISS a specificity of 52% (in all severities). Conclusion: Combining novel TBI biomarkers H-FABP and IL-10 with GFAP, NF-L and S100B and clinical parameters improves outcome prediction models in TBI.